Image filtration in Python using openCV - et. al., Sahil Singh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Image processing is an area consisting of different phases for manipulating pixels of an image. Image processing is an enhancement of images which affects an image's pictorial view. Image processing is the process of converting an image into digital form and then performing various operations on it, such as enhancing the image or extracting useful information. Image filtering is a technique for altering the scale, shape, color, depth, smoothness, and other aspects of images. Essentially, it modifies the pixels of an image to transform it into the desired form using various types of graphical editing methods via graphic design and editing software. In Image Improvement, the removal of noise is very necessary and filters are used for this. This paper introduces some filters that will give you a better version of your image. Using different kinds of filters provides you noise free images.